Monitoring of hard ticks at urban recreational sites in the City of Zagreb from 2016 to 2018 : Praćenje tvrdih krpelja u urbanim rekreacijskim odredištima grada Zagreba od 2016. do 2018. godine - Vucelja, Marko (Array, 2020)
As tick-borne disease incidence and distribution is increasing worldwide, there is a true need for better understanding of the distributional ecology of their vectors. The aim of this study was to determine the diversity of hard ticks fauna (Acari: Ixodidae) and their seasonal dynamics in different habitats at three urban recreational sites in Croatia’s capital, the City of Zagreb, known as the natural foci of Lyme borreliosis and tick borne encephalitis. Within a three-year period (2016 - 2018), the only species detected was Ixodes ricinus Linnaeus, 1758. Using flag dragging method 506 ticks were sampled; 273 (54%) in their nymphal stage, 166 (33%) as larvae and 64 (13%) as adults. The highest abundance of ticks was recorded at forest habitat. Seasonal activity showed their peaks at midspring and midsummer. Continuous monitoring of hard tick population in urban areas should and could become a standard method of tick-borne diseases prevention.